2017
DOI: 10.1186/s40795-017-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

High magnitude of under nutrition among HIV infected adults who have not started ART in Tanzania--a call to include nutrition care and treatment in the test and treat model

Abstract: Background: Undernutrition among people living with HIV (PLWHIV) can be ameliorated if nutrition specific and sensitive interventions are integrated into their HIV care and treatment centers (CTC). Integrated care is lacking despite expansion of antiretroviral therapy (ART) coverage, representing a substantial missed opportunity. This research aims to examine nutritional status and associated risk factors among HIV-positive adults prior to ART initiation in Tanzania in order to characterize existing gaps and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Our analysis has shown that the severity of malnutrition is higher among female PLHIV. This finding concurred with other studies conducted in Ethiopia (Daniel et al, 2013), Tanzania (Sunguya et al, 2017), and Zimbabwe (Takarinda et al, 2017), which have demonstrated that female PLHIV were more affected by malnutrition. The possible reason for females to become more malnourished than males may be that females take care of their household vis-à-vis diet preparation as well as prioritizing food for their children and to their family members instead of taking care of themselves.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our analysis has shown that the severity of malnutrition is higher among female PLHIV. This finding concurred with other studies conducted in Ethiopia (Daniel et al, 2013), Tanzania (Sunguya et al, 2017), and Zimbabwe (Takarinda et al, 2017), which have demonstrated that female PLHIV were more affected by malnutrition. The possible reason for females to become more malnourished than males may be that females take care of their household vis-à-vis diet preparation as well as prioritizing food for their children and to their family members instead of taking care of themselves.…”
Section: Discussionsupporting
confidence: 92%
“…Analogous to this finding, the study conducted in other parts of Ethiopia indicated that lowest asset possession is associated with malnutrition (Weldehaweria et al, 2017). On the other hand, higher wealth index was found associated with better nutritional status, and is less likely to exhibit malnutrition compared with their counterparts (Sunguya et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Subjects who had a CD4 cell count of 200–349 cells/mm 3 had a better DD than those who had CD4 cell counts less than 200 cells/mm 3 . This was due to poor nutritional status (particularly micronutrients can lead to immunosuppression), advanced HIV clinical stage, or disturbance of the metabolic system and loss of appetite ( 28 ) . This was similar to the study done in Uganda, which reveals that consumption of diversified diet was positively associated with higher CD4 cell count ( 29 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary Diversity Scores were calculated by taking the sum of foods group consumed in the day that preceded the interview. Dietary diversity scores below three were considered low dietary intake, otherwise high (21,22). This tools is useful proxy indicator of nutrient adequacy of marginalized populations including rural elderly people in Sri lanka as indeed, the performance of the indicators is improved when considering the quantities of food consumed (23).…”
Section: Variables and Outcome Measuresmentioning
confidence: 99%
“…This includes safe water, food, health services, and education. Owning some important properties is an indicator of how wealthier a person can be and can also facilitate and improve the quality of life thereof (22,33,34).…”
Section: Factors Associated With Hrqolmentioning
confidence: 99%